Sekolah Ibu Hebat: Membangun Resiliensi Keluarga di Era Digital - Dwi Susanto; Syafrina Sari Lubis (Rengganis Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to enhance family resilience through the development of the strategic potential of the millennial mothers’ community in the Sekolah Ibu Hebat program in Jambangan District, Surabaya. The program was implemented using the Asset-Based Community Development (ABCD) approach, consisting of the stages of enculturation, discovery, design, define, and reflection. The community service activities were conducted over a three-month period, from January to March 2025, involving 35 millennial mothers who are members of the Sekolah Ibu Hebat community under Rumah Keluarga Indonesia. The main issues faced by the target community included low digital literacy, limited parenting skills, inadequate family financial management, and restricted social support networks for families. Data were collected through observation, in-depth interviews, Focus Group Discussions (FGDs), and activity documentation. The results of the program showed a 68% improvement in participants’ digital literacy skills, a 74% increase in parenting understanding, and the establishment of a community-based social support network that strengthened emotional support among members. In addition, 80% of participants reported greater confidence in managing their families in the digital era. The program also produced several outputs, including a digital parenting module, family mentoring groups, and an online communication forum for the millennial mothers’ community. This community service initiative demonstrates that the ABCD approach is effective in strengthening community participation while enhancing family resilience through the optimization of the social, cultural, and digital assets within the community. The program also has a positive impact on family resilience, particularly in navigating the dynamics of modern family life in the digital era.